The Effect of Special Training For Developing Some Regression Abilities in Advanced Soccer Players Recovering from Adductor Muscle Tear - Saleem, Ismael; Hanoon, wasan (Journal of Physical Education, 2019)
The research aimed at designing special training for developing (agility, strength – endurance, speed – endurance). In addition to that, the research aimed at identifying the effect of these training on developing these regressive abilities on players returning from adductor muscle tear. The researchers hypothesized statistical differences between pre and posttests in regressive abilities development. The data was collected and treated using SPSS to conclude that the experimental method have a positive effect in developing regressive abilities understudy. The researchers finally recommended the necessity of strength training for all muscle groups especially weak or small muscles as well as paying attention to transitional phase with short passive rests and coordinating between the 1st coach and physical fitness coach during training programs design.